Experimental facility IHEPNP for fundamental and applied researhes in energy range up to 100 MeV - Ganenko, V.B.; Kasilov, V.I.; Kovalenko, G.D.; Maslov, N.I.; Semisalov, I.L. (Вопросы атомной науки и техники, 2020)
The possibility of creating an experimental setup in building No.3 of the IHEPNP NNC KIPT (LUE-300 complex) on the basis of the existing LUE-60 electron accelerator and the existing experimental infrastructure is being discussed. It is planned to raise the energy of the electron beam to 100 MeV and create two beam lines: one is for reaserches with intense beams of electrons and photons, including linearly polarized ones, and the other – for investigations with the low intensive beams of electrons and positrons. Implementation of the project will open opportunities for a wide range of research programs in the field of interaction of the radiation with amorphous and crystalline matter, nuclear physics and astrophysics, as well as in the applied research. Обговорюється можливість створення експериментальної установки в будівлі №3 ІФВЕЯФ ННЦ ХФТІ (прискорювальний комплекс ЛУЕ-300) на основі чинного прискорювача електронів ЛУЕ-60 і існуючої експериментальної інфраструктури. Планується збільшити енергію електронного пучка до 100 МеВ і створити дві пучкові лінії: одну для досліджень з інтенсивними пучками електронів і фотонів, у тому числі лінійно поляризованих, а іншу – для досліджень з пучками електронів і позитронів низької інтенсивності. Реалізація проекту відкриє можливості для виконання дослідницьких програм в області взаємодії випромінювання з аморфною речовиною і кристалами, в галузі ядерної фізики і астрофізики, а також прикладних досліджень. Обсуждается возможность создания экспериментальной установки в здании №3 ИФВЭЯФ ННЦ ХФТИ (ускорительный комплекс ЛУЭ-300) на основе имеющегося ускорителя электронов ЛУЭ-60 и существующей экспериментальной инфраструктуры. Планируется увеличить энергию электронного пучка до 100 МэВ и создать две пучковые линии: одну для исследований с интенсивными пучками электронов и фотонов, в том числе линейно поляризованных, а другую – для исследований с пучками электронов и позитронов низкой интенсивности. Реализация проекта откроет возможности для выполнения исследовательских программ в области взаимодействия излучения с аморфным веществом и кристаллами, в области ядерной физики и астрофизики, а также прикладных исследований.